Estimation of the Postmortem Duration of Mouse Tissue by Electron Spin Resonance Spectroscopy - Shinobu Ito; Tomohisa Mori; Hideko Kanazawa; Toshiko Sawaguchi (Journal of Toxicology)
Electron spin resonance (ESR) method is a simple method for detecting various free radicals simultaneously and directly. However, ESR spin trap method is unsuited to analyze weak ESR signals in organs because of water-induced dielectric loss (WIDL). To minimize WIDL occurring in biotissues and to improve detection sensitivity to free radicals in tissues, ESR cuvette was modified and used with 5,5-dimethtyl-1-pyrroline N-oxide (DMPO). The tissue samples were mouse brain, hart, lung, liver, kidney, pancreas, muscle, skin, and whole blood, where various ESR spin adduct signals including DMPO-ascorbyl radical (AsA∗), DMPO-superoxide anion radical (OOH), and DMPO-hydrogen radical (H) signal were detected. Postmortem changes in DMPO-AsA∗ and DMPO-OOH were observed in various tissues of mouse. The signal peak of spin adduct was monitored until the 205th day postmortem. DMPO-AsA∗ in liver (y=113.8–40.7 log (day), R1=-0.779, R2=0.6, P<.001) was found to linearly decrease with the logarithm of postmortem duration days. Therefore, DMPO-AsA∗ signal may be suitable for detecting an oxidation stress tracer from tissue in comparison with other spin adduct signal on ESR spin trap method.